Measurement of Γee(J/ψ) with KEDR detector - V. V Anashin (Journal of High Energy Physics, 2018)
Abstract The product of the electronic width of the J/ψ meson and the branching fractions of its decay to hadrons and electrons has been measured using the KEDR detector at the VEPP-4M e + e − collider. The obtained values are ΓeeJ/ψ=5.550±0.056±0.089keV,ΓeeJ/ψ·ℬhadronsJ/ψ=4.884±0.048±0.078keV,ΓeeJ/ψ·ℬeeJ/ψ=0.3331±0.0066±0.0040keV. $$ \begin{array}{c}\hfill {\Gamma}_{ee}\left(J/\psi \right)=5.550\pm 0.056\pm 0.089\kern0.5em \mathrm{keV},\hfill \\ {}\hfill {\Gamma}_{ee}\left(J/\psi \right)\cdotp {\mathrm{\mathcal{B}}}_{\mathrm{hadrons}}\left(J/\psi \right)=4.884\pm 0.048\pm 0.078\kern0.5em \mathrm{keV},\hfill \\ {}\hfill {\Gamma}_{ee}\left(J/\psi \right)\cdotp {\mathrm{\mathcal{B}}}_{ee}\left(J/\psi \right)=0.3331\pm 0.0066\pm 0.0040\kern0.5em \mathrm{keV}.\hfill \end{array} $$ The uncertainties shown are statistical and systematic, respectively. Using the result presented and the world-average value of the electronic branching fraction, one obtains the total width of the J/ψ meson: Γ=92.94±1.83keV. $$ \Gamma =92.94\pm 1.83\kern0.5em \mathrm{keV}. $$ These results are consistent with the previous experiments.